HEPARIN-INDUCED THROMBOCYTOPENIA - Kopytsa, N.P.; Lytvyn, O.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
This review considers heparin-induced thrombocytopenia (HIT) – pathological condition that can develop when applying non-fractionated heparin (NFH). Due to insufficient knowledge and absence of required laboratory tests HIT is a rarely diagnosed condition in our clinics that influences on the adequate treatment of patients and prognosis. In vitro studies demonstrated that immune processes like forming HIT-antibodies and their interaction with heparin-tissue factor-4 complex and FcγRII-receptors on the platelets is the key moment in HIT. A big disadvantage is inability to get alternative anticoagulants. Management of hemorrhage in HIT especially without antidote is problematic. Applying heparins with low molecular weight and fondaparinux and direct thrombin inhibitors instead of NFH can result in that the HIT will become only a past history event.